SOCIO-ENVIRONMENTAL VULNERABILITY OF CENSITIVE SECTORS INTO THE MARGINS OF THE POTI RIVER, TERESINA-PIAUÍ-BRAZIL - Nunes, Hikaro Kayo de Brito (2020)
The objective of this study is to analyze the socio-environmental vulnerability of the census tracts bordering the Poti River in the municipality of Teresina (Piauí/Brazil). From the use use of geoprocessing tools and field and laboratory activities, the crossing of 7 socioeconomic variables and 12 environmental variables to obtain socio-environmental vulnerability. The 72 census tracts were grouped into 4 classes of Socio-Environmental Vulnerability (IVSA): IVSA Very High (33% of the area), High (10% of the area), Medium (17% of the area) and Low (33%), besides the insufficient data of 7% of the sectors. In general, the census tracts located in the Center-North and part of the Southeast region were identified as the most vulnerable areas, requiring greater public attention.